Medieval Irish chronicles reveal persistent volcanic forcing of severe winter cold events, 431–1649 CE - Francis Ludlow; Alexander R Stine; Paul Leahy; Enda Murphy; Paul A Mayewski; David Taylor; James Killen; Michael G L Baillie; Mark Hennessy; Gerard Kiely (Environmental Research Letters, 2013)
Explosive volcanism resulting in stratospheric injection of sulfate aerosol is a major driver of regional to global climatic variability on interannual and longer timescales. However, much of our knowledge of the climatic impact of volcanism derives from the limited number of eruptions that have occurred in the modern period during which meteorological instrumental records are available. We present a uniquely long historical record of severe short-term cold events from Irish chronicles, 431–1649 CE, and test the association between cold event occurrence and explosive volcanism. Thirty eight (79%) of 48 volcanic events identified in the sulfate deposition record of the Greenland Ice Sheet Project 2 ice-core correspond to 37 (54%) of 69 cold events in this 1219 year period. We show this association to be statistically significant at the 99.7% confidence level, revealing both the consistency of response to explosive volcanism for Ireland’s climatically sensitive Northeast Atlantic location and the large proportional contribution of volcanism to historic cold event frequencies here. Our results expose, moreover, the extent to which volcanism has impacted winter-season climate for the region, and can help to further resolve the complex spatial patterns of Northern Hemisphere winter-season cooling versus warming after major eruptions.